Highly Efficient Deposition of Centimeter‐Scale MoS2 Monolayer Film on Dragontrail Glass with Large Single‐Crystalline Domains. Issue 12 (26th October 2022) - Yang, Xu; Li, Shisheng; Sakuma, Yoshiki
Abstract: Highly efficient growth of a centimeter‐scale MoS2 monolayer film by oxide scale sublimation chemical vapor deposition (OSSCVD) in a time as short as 60 s is reported. Benefiting from the superior catalytic ability of Dragontrail glass (DT‐glass) substrate and the controlled large vapor supersaturation of the molybdenum source, the ultrafast deposition of MoS2 is realized with maintaining large‐sized single‐crystalline domains over 20 µm at maximum in the film. It is comparable to those reported for MoS2 grown in tens of minutes and even hours. Similar to the face‐to‐face precursor feed route, the gas‐controlled OSSCVD with a showerhead configuration facilitates a homogeneous and controllable source supply. It enables high‐quality monolayer MoS2 film deposition on 2 × 2 cm 2 DT‐glass with centimeter‐scale uniformity confirmed by microscopic, spectroscopic, and electrical characterizations. Back‐gate MoS2 field‐effect transistors fabricated on polycrystalline continuous film exhibit the maximum field‐effect mobility of 5.1 cm 2 V −1 s −1 and a peak I on / I off ratio of 5 × 10 8 . They reach 40 cm 2  V −1  s −1 and 1.2 × 10 9, respectively, on single‐crystalline domains. These results are even greater than those for MoS2 grown using 1–2 orders of magnitude longer deposition time and higher temperatures. This study highlights the opportunities for low‐cost high‐throughput production of large‐area high‐quality monolayer MoS2 . Abstract : Ultrafast chemical vapor deposition of a high‐quality large‐area MoS2 monolayer film is achieved in 60 s using Dragontrail glass as a catalytic substrate. This is among the shortest time to form a continuous centimeter‐scale MoS2 monolayer film. The growth shows good spatial homogeneity, superior crystallinity, and decent electrical properties comparable to those for MoS2 grown using 10–100 times longer deposition time.